Hubungan Self Management dengan Sikap Bullying Peserta Didik di Kelas XI BDP SMK Negeri 1 Painan Kabupaten Pesisir Selatan - Pratiwi Mai Putri; Rici Kardo; Rila Rahma Mulyani (Journal on Education, 2023)
The background of this research is because the purpose of the research is to describe; 1) Self-management of class XI students 2) Bullying attitudes of class XI students 3) The relationship between self-management and bullying attitudes of class XI students. This research is a type of quantitative descriptive research with a correlation analysis approach. Data collection in this study used a questionnaire instrument. The population of this study was all students of class XI BDP SMK Negeri 1 Painan totaling 92 people. The sampling technique used a total sampling of 92 people. Data analysis using correlation techniques. The results of this study reveal that 1) Self-management of class XI students is in the fairly good category, 2) The bullying attitude of class XI students is in the fairly good category, 3) The relationship between self-management and bullying attitudes of class XI students is in the very category weak. Based on this research, it is recommended for counseling teachers and subjects to improve self-management and reduce bullying attitudes. Based on the relationship between self-management and bullying attitudes, it is in the very good category.